2013
DOI: 10.1016/j.jacc.2013.04.088
|View full text |Cite
|
Sign up to set email alerts
|

Patients With Heart Failure Have an Increased Risk of Incident Cancer

Abstract: Objective To evaluate the risk of cancer in patients with heart failure (HF) compared to community controls and its impact on outcome. Background HF is associated with excess morbidity and mortality. Non-cardiac causes of adverse outcomes in HF are increasingly recognized but not fully characterized. Methods In a case-control study, we compared history of cancer among community subjects newly diagnosed with HF from 1979–2002 to age-, sex-, and date-matched community controls without HF (961 pairs). Individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
165
1
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 205 publications
(190 citation statements)
references
References 27 publications
14
165
1
10
Order By: Relevance
“…The increased incidence of cancer observed in the present study is in agreement with a recent study of 596 American HF patients, which reported a 60% increased risk of cancer. The risk remained increased after adjustment for shared risk factors such as smoking and body mass index . Even though our cohort was ∼5 years younger, with an average age of 67.8 years compared with the American cohort, the two cohorts were comparable with regard to co‐morbidities such as diabetes and prior myocardial infarction.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The increased incidence of cancer observed in the present study is in agreement with a recent study of 596 American HF patients, which reported a 60% increased risk of cancer. The risk remained increased after adjustment for shared risk factors such as smoking and body mass index . Even though our cohort was ∼5 years younger, with an average age of 67.8 years compared with the American cohort, the two cohorts were comparable with regard to co‐morbidities such as diabetes and prior myocardial infarction.…”
Section: Discussionmentioning
confidence: 75%
“…With cancer being a major source of morbidity and mortality and a recent study suggesting an increased risk of cancer among American chronic HF patients, the aim of the present study was to assess the incidence and risk of major types of cancer in a large Danish cohort with HF compared with the general population by using nationwide Danish administrative registries with complete follow‐up. In addition, this study reviewed the prognosis after a diagnosis of cancer in patients with HF compared with the background population.…”
Section: Introductionmentioning
confidence: 99%
“…Although usually considered a separate cause of morbidity, it may be that an association exists between heart disease and an increased risk of cancer. Our group has indeed shown a 70% increased risk of cancer among HF patients in Olmsted County, Minnesota compared with community controls (3). In that study, controls were matched to HF patients by age and sex, and efforts were made to comprehensively adjust for other recognized factors.…”
Section: Introductionmentioning
confidence: 69%
“…We previously reported an increased risk of cancer among HF patients as compared with community controls (3). In the present, study, the HF and non-HF patients shared many of the risk factors, diagnostic procedures, and medications because all patients were survivors of MI.…”
Section: Discussionmentioning
confidence: 99%
“…20 In line with this current significant independent inverse association of HbA 1c with LVEF among diabetic patients and an insignificant trend to positive association in nondiabetic subjects, prediction herein of a composite endpoint comprising both HF and malignancy further supports the report that patients with HF have an increased risk of incident cancer. 21 …”
Section: Discussionmentioning
confidence: 99%